Comparison between vitamin E plasma level in diabetic retinopathy and normal person - Tri Wahyu Widayanti, Tri Wahyu Widayanti (Universitas Gadjah Mada, 1997)
Diabetic retinopathy is one of the late complications of diabetes mellitus. Recent data have suggested that free radicals possibly play a role in its pathophysiology. Oxidative stress is very high in hyperglycemic condition leading to increased lipid peroxidation of the phospholipid cell membrane. Vitamin E is a chain breaking membrane antioxidant which can prevent lipid peroxidation in the cell membrane. The study was aimed at determining vitamin E plasma level in diabetic retinopathy compared to healthy subjects. In this study vitamin E plasma level in 30 diabetic retinopathy patients and 30 healthy subjects were measured by using (HPLC) technique. The result showed that the mean of vitamin E plasma level in healthy subjects and patients with diabetic retinopathy are 5.09 ± 3.51 and 4.32 ± 2.75 µg/ml respectively (Student t-test, p > 0.05) Total lipid level has a significant influence in increasing the vitamin E plasma level with coefficient correlation r=0.9746 and p<0.01. Further studies are needed to clasify factors that influence vitamin E plasma levels.Keywords: vitamin E - diabetic retinopathy - oxidative stress - lipid peroxidation